Pengaruh Konten Positif Media Sosial Tiktok Terhadap Peningkatan Self Healing (Survei pada akun @aldila.aap) - Yuliarti, Herlina; Wati, Lina; Fornawati , Sri Murdilah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to determine whether there is an influence of positive content in the @aldila.aap tiktok account and how much influence it has on increasing followers' self-healing. This study uses a positivism paradigm descriptive quantitative research type, data collection techniques obtained through distributing questionnaires using google form. Researchers used simple linear regression analysis and the coefficient of determination and processed using SPSS 25. The population in this study were followers of @aldila.aap with a sample calculation of 100 respondents, and used purposive sampling. Researchers use uses and gratification theory, the assumption of this theory emphasises the active role of users where users actively choose and use media to meet their needs and goals. The results of this study indicate that there is a positive influence in the tiktok account @aldila.aap on increasing self-healing indicated by the results of the T test which shows 8.368> t table 1.664 and 0.000 <0.05 that the positive content @aldila.aap has a positive and significant effect on increasing followers' self-healing. In the coefficient of determination test, the data results show a value of 0.417 or 41.7%, which means that the variable that occurs to increase self-healing followers is caused by the positive content variable @aldila.aap, the rest is influenced by other variables or outside the study.